2004
DOI: 10.1002/hep.20248
|View full text |Cite
|
Sign up to set email alerts
|

Covalent modification as a mechanism for the breakdown of immune tolerance to pyruvate dehydrogenase complex in the mouse

Abstract: The autoimmune liver disease primary biliary cirrhosis (PBC) is characterized by the breakdown of normal immune self tolerance to pyruvate dehydrogenase complex (PDC). How tolerance is broken to such a central and highly conserved self antigen in the initiation of autoimmunity remains unclear. One postulated mechanism is that reactivity arises to an altered form of self antigen with subsequent cross-reactivity to native self. In this murine study, we set out to examine whether sensitization with a covalently m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 46 publications
1
16
0
Order By: Relevance
“…Furthermore, we have previously demonstrated that rabbits immunized with a xenobiotic-hapten, 6BH-BSA, produced self-AMA that had all the characteristics of human AMA in that they recognized PDC-E2, BCOADC-E2, and OGDC-E2 and inhibited PDC enzyme activity (9). Similarly, s.c. immunization of SJL/J mice with biotinylated murine PDC produced Ab and T cell reactivities to unmodified and modified murine PDC (25). Although mild inflammation in the portal tract was seen in immunized SJL/J mice, both the rabbit and the SJL mice model fall short of any evidence of the bile duct injury, cholestasis, or fibrosis that are characteristic of PBC livers (9).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we have previously demonstrated that rabbits immunized with a xenobiotic-hapten, 6BH-BSA, produced self-AMA that had all the characteristics of human AMA in that they recognized PDC-E2, BCOADC-E2, and OGDC-E2 and inhibited PDC enzyme activity (9). Similarly, s.c. immunization of SJL/J mice with biotinylated murine PDC produced Ab and T cell reactivities to unmodified and modified murine PDC (25). Although mild inflammation in the portal tract was seen in immunized SJL/J mice, both the rabbit and the SJL mice model fall short of any evidence of the bile duct injury, cholestasis, or fibrosis that are characteristic of PBC livers (9).…”
Section: Discussionmentioning
confidence: 99%
“…153 Importantly, the immunization of SJL/J mice with covalently modified self PDC-E2 could elicit the breakdown of both T-and B-cell tolerance. 154 Lastly, and most recently, one common everyday additive, 2-octynoic acid, was identified by Amano et al 155 as a common antigen in PBC sera.…”
Section: Molecular Mimicrymentioning
confidence: 99%
“…Among the events demonstrated to induce an antibody response cross-reactive with self-PDC are exposure to bacterial PDC 9,10 or other microbial structural mimics 34 and exposure to chemically modified PDC or mimicking xenobiotics. 35,36 Other potential events currently lacking demonstration of direct in vivo priming are exposure to PDC components modified during caspase cleavage in cells undergoing apoptosis 37 and exposure to cross-reactive retroviral proteins. 38 The diversity of the potential events giving rise to antibody responses cross-reactive with PDC, which could promote subsequent T-cell tolerance breakdown, suggests the intriguing possibility that PBC could represent a condition with a common final pathway (T-cell tolerance breakdown and target cell damage) but with multiple triggers .…”
Section: Discussionmentioning
confidence: 99%